SOSIALISASI KEARIFAN LOKAL DALAM BUDAYA JAWA BAGI SISWA SEKOLAH DASAR DI DAERAH ISTIMEWA YOGYAKARTA - Siti Partini Suardiman (Jurnal Kependidikan, 2007)
There was an indication that cultural local wisdoms in theJavanese culture became limited, isolated, not recognized, andeven not “communicable” around the youth, so that localwisdoms were only part of the past. The purpose of the presentstudy was to develop teaching resources as supplement forexisting student textbooks to re-socialize Javanese culture localwisdoms for elementary school students. The study wasconducted by use of the research and development method. Thelocal wisdom material was found from older citizens who werepotential to keep the local wisdom wealth, by deep interview, orfrom articles or literatures (documents). Before being tried out,the material was validated by Javanese Language experts.Translation into the Javanese language was done by a seniorteacher (retired Elementary School Headmaster). Limited tryoutwas done for Sixth-grade elementary school students. Thestudy yielded a set of teaching resources containing variantidentifications of local wisdoms found in stories relevant withchildren’s condition. The teaching resources were ready to besocialized for elementary school students, specially the sixthgraders, as one of the efforts to treasure local wisdoms.